Non-specificity of sequence characterised amplified region as an alternative molecular epidemiology marker for the identification of Salmonella enterica subspecies enterica serovar Typhi - Ja’afar Nuhu Ja’afar; Subhash Janardhan Bhore; Kia Kien Phua (BMC Research Notes, 2018)
Abstract Objective Identification of Salmonella Typhi by conventional culture techniques is labour-intensive, time consuming, and lack sensitivity and specificity unlike high-throughput epidemiological markers that are highly specific but are not affordable for low-resource settings. SCAR, obtained from RAPD technique, is an affordable, reliable and reproducible method for developing genetic markers. Hence, this study investigated the use of SCAR as an alternative molecular epidemiological marker for easy identification of S. Typhi in low-resource settings. Results One hundred and twenty RAPD primers were screened through RAPD-PCR against a panel of common enterobacteriaceae for the best RAPD band pattern discrimination to develop SCAR primers that were used to develop a RAPD-SCAR PCR. Of this number, 10 were selected based on their calculated indices of discrimination. Four RAPD primers, SBSA02, SBSA03, SBSD08 and SBSD11 produced suitable bands ranging from 900 to 2500 bp. However, only SBSD11 was found to be specific for S. Typhi, and was cloned, sequenced and used to design new SCAR primers. The primers were used to amplify a panel of organisms to evaluate its specificity. However, the amplified regions were similar to other non-Typhi genomes denoting a lack of specificity of the primers as a marker for S. Typhi.